Analisis Pengetahuan Ibu Nifas dengan Tanda Bahaya Masa Nifas di Bidan Praktik Mandiri Massiana Kabupaten Sintang - Arum, Rizki Yolanda; Masan, Lea; Haryanti, Yunida; Lestari, Arum Seftiani; Pratiwi, Dian Ika; Montessori, Yolanda; Kurniati, Paskatalia Tri; Rahayu, Ngaisah Tri; Saniati, Khairulisni; Juliansyah, Elvi; Akhmad, Akhmad (Jurnal Kesehatan Indonesia, 2024)
Maternal Mortality Rate (MMR) is an indicator for improving health status and the success of implementing health development. Maternal Mortality Rate (IMR) is the number of women who die during pregnancy, childbirth and the postpartum period (42 days after giving birth) due to pregnancy abnormalities and their management. Based on 2018 SRS (Sampling Registration System) data, it is known that around 36% of maternal deaths occurred when the mother was in the labor phase, 40% of maternal deaths occurred during the postpartum period, and 34% of maternal deaths occurred during pregnancy. (Indonesian Ministry of Health, 2019). The aim of the research is to find out the relationship between postpartum mothers' knowledge and danger signs during the postpartum period. The research object is the knowledge of postpartum mothers about the danger signs of postpartum, quantitative descriptive research method, cross sectional approach, population of 35 postpartum mothers at PMB Massiana, sample of 35 postpartum mothers at PMB Massiana, total sampling technique, data analysis used by Chi Sguare. There is a relationship between the knowledge of postpartum mothers and the danger signs during the postpartum period with a P value of 0.007 and an Odd Ratio value of 2.084. The conclusion is that postpartum mothers who have sufficient knowledge are 2.084 times more likely to experience one of the danger signs during the postpartum period compared to postpartum mothers who have good knowledge.